Pengembangan Media Pembelajaran Flipbook untuk Meningkatkan Kemampuan Menyimak pada Teks Berita Siswa Kelas VII SMP Negeri 1 Bawolato - Faona’atulo Harefa; Lestari Waruwu; Yanida Bu’ulolo; Noveri Amal Jaya Harefa (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The purpose of this study was to develop flipbook learning media to improve listening skills in news texts of class VII students of SMP Negeri 1 Bawolato. The implementation procedure or research method used is Research and Development (R&D) with the Borg and Gall model, which includes ten stages ranging from potential and problems to mass production. The subjects in this study were class VII students of SMP Negeri 1 Bawolato, even semester class VII-A totaling 6 people, 3 boys and 3 girls, class VII-B totaling 31 people, 17 boys and 14 girls. The results of the study showed that the flipbook media had been validated by three experts, namely material, language, and design experts with a percentage level of 100% for each aspect tested so that it was categorized as "very feasible" to use. The practicality test conducted on a small group showed that the flipbook scored 96.21% which means "very practical" in its use. In addition, the results of the effectiveness test conducted on a large group showed an effectiveness level of 83.87% which was categorized as "very effective" in improving students' listening skills. It was concluded that flipbook learning media to improve listening skills in news texts was very feasible, practical, and effective in supporting learning to listen to news texts in class VII. It is hoped that further researchers will use this research as additional insight to carry out research.